The impact of confirmation bias awareness on mitigating susceptibility to misinformation - Piksa, Michal; Noworyta, Karolina; Gundersen, Aleksander; Kunst, Jonas; Morzy, Mikolaj; Piasecki, Jan; Rygula, Rafal (Frontiers in Public Health, 2024)
In the current digital age, the proliferation of misinformation presents a formidable challenge to a democratic society. False narratives surrounding vaccination efforts pose a significant public health risk. Understanding the role of cognitive biases in susceptibility to misinformation is crucial in addressing this challenge. Confirmation bias, characterized by the tendency to favor information that aligns with pre-existing beliefs or attitudes, can exacerbate the spread of false narratives.This study investigates the effect of confirmation bias awareness on susceptibility to general misinformation. For this, a sample of 1479 participants was recruited, ensuring diverse representation across attitudes towards vaccination. Half of the participants received targeted information about confirmation bias, aimed at increasing awareness of this bias and its potential impact on cognitive processing of information. The other half did not receive this information.Results from the study indicated that participants exposed to an intervention aimed at inducing awareness of confirmation bias demonstrated reduced susceptibility to misinformation and increased ability to general discernment of veracity. Notably, these effects were only pronounced among individuals who initially were most negative towards COVID-19 vaccines.These insights provide a foundation for developing targeted strategies to promote informed decision-making and mitigate the spread of misinformation, particularly in the context of public health crises. Further research is warranted to explore the underlying mechanisms driving these effects and to refine intervention approaches for diverse populations and contexts.